Glacial Troughs Enhance Shelf/Slope Exchange in the Barotropic Limit. Issue 6 (16th June 2022) - Hampson, Patrick M.; Pringle, James M.
Abstract: Glacial troughs are flat‐bottomed, steep‐sided submarine valleys that incise the shelf and significantly alter coastal circulation. We examine how these features drive exchange between the shelf and the slope in the barotropic and linear limits. When the alongshore flow is in the Kelvin‐wave (downwave/downwelling favorable) direction, the troughs move transport from the shelf upwave of the trough to the slope downwave of the trough, diminishing wind‐driven alongshore transport on the shelf downwave of the trough. Conversely, when the alongshore flow is against the Kelvin wave direction (upwave/upwelling favorable), the troughs move transport from the slope downwave of the trough to the shelf upwave of the trough. These cross‐shelf flows are driven by the acceleration and curvature of the flows induced by the narrowing and turning isobaths around the trough, and the bottom friction experienced by these accelerated flows. These dynamics are quantified by examining the along‐isobath evolution of potential vorticity in the model's limits. Plain Language Summary: A specific type of submarine valley, the glacial trough, is shown to alter how ocean currents behave within the coastal environment. Computational modeling is used to explore how troughs of different sizes and shapes impact coastal circulation for typical coastal currents in the limit of uniform density water. Results from this model demonstrate that troughs change coastal circulation by moving waters either from the shelf to the deeper slope or the reverse. The direction of water transfer depends on the direction the water is flowing and the size of the trough. The relative importance of the mechanisms responsible for these dynamics are quantified, and an analysis of the significance of this phenomenon is given. Key Points: Glacial troughs drive offshore exchange from shelf to slope for downwave/downwelling flows, and onshore exchange for upwelling/upwave flows Trough bathymetry leads to converging isobaths and acceleration of along‐isobath flows Accelerated flows lead to increased bottom drag and enhanced cross‐isobath transport